Perancangan Interior Shop and Play Airsoftgun di Trawas dengan Konsep âWar of Iwojimaâ - Buana, Eleazar Prawira (Intra, 2014)
âShop and Play Airsoft Gunâ in Trawas which is one of many place that people that still at teen or adult can spend their time for their daily sport or even stimulate their adrenaline. This place can also help them not only for daily sport, but this place can help them to think of a strategy to win their batle with another team, But âShop and Play Airsoft Gunâ not only to make our life healthy, but also to introduce to Indonesia that airsoft gun is a tool for play and sports, not for act of crime. Also with the education for new player that want to know about airsoft gun.Â âShop and Play Airsoft Gunâ Have e thematic design, which are World War II so that its give many atraction to people to come. But because this game is dangerous for kids, this game must be limited to 17 years above, so that there is no harm and accident happened in the process of the game.